2016
DOI: 10.1364/boe.7.004941
|View full text |Cite
|
Sign up to set email alerts
|

Robust respiration detection from remote photoplethysmography

Abstract: Continuous monitoring of respiration is essential for early detection of critical illness. Current methods require sensors attached to the body and/or are not robust to subject motion. Alternative camera-based solutions have been presented using motion vectors and remote photoplethysmography. In this work, we present a non-contact camera-based method to detect respiration, which can operate in both visible and dark lighting conditions by detecting the respiratory-induced colour differences of the skin. We make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 29 publications
(48 reference statements)
0
86
1
Order By: Relevance
“…5 healthy adults (2 female) (aged 29-38 years, M=31.4, SD=3.78) were recruited from the university subject pool. Following the protocol used in [5], participants were asked to maintain a stable posture and breath according to a set of breathing patterns presented to them on a screen. Figure 5 shows the design for this experiment.…”
Section: Dataset 1: Controlled Respiration In Environments With Non-cmentioning
confidence: 99%
See 1 more Smart Citation
“…5 healthy adults (2 female) (aged 29-38 years, M=31.4, SD=3.78) were recruited from the university subject pool. Following the protocol used in [5], participants were asked to maintain a stable posture and breath according to a set of breathing patterns presented to them on a screen. Figure 5 shows the design for this experiment.…”
Section: Dataset 1: Controlled Respiration In Environments With Non-cmentioning
confidence: 99%
“…Despite its importance, it has been largely disregarded in real world healthcare technology applications [3]. One possible reason is the inconvenience of conventional respiration measurement systems, such as chest-belts or oronasal probes, which demand direct physical contact [4][5][6]. These systems are often uncomfortable to wear and prone to motion artifacts which might cause incorrect sensor readings.…”
Section: Introductionmentioning
confidence: 99%
“…This picture is complicated somewhat by respiratory activity as, first, intra-thoracic pressure variations cause an exchange of blood between the pulmonary and the systemic circulation which results in a variation of perfusion baseline which adds an offset to the heart rate signal. In addition, a decrease in cardiac output due to reduced ventricular filling causes pulse amplitude variations that provide a respiratory induced amplitude modulation (AM) to the heart rate signal [20]. Here the former is removed by filtering and the latter by standard demodulation methods.…”
Section: The Cppg Signal C(t)mentioning
confidence: 99%
“…However, none of these previous methods directly estimated and evaluated physiological metrics from NIR frames. One exception is the works of van Gastel et al, which considered NIR face videos to estimate HR and BR [11,12]. In their study, they observed that the relative photoplethysmographic amplitude was significantly reduced in NIR compared to visible light and, therefore, they needed to use three NIR wavelengths (hence three NIR cameras with different optical filters) to appropriately separate pulse-induced intensity variations from motion artifact.…”
Section: Previous Workmentioning
confidence: 99%